Diseño de un sistema de generación de energía fotovoltaico para suplir las necesidades de energía eléctrica en la finca “Torre Solar”, ubicada en zona rural del municipio de Turbaco Bolívar (2022)
A photovoltaic power generation system was designed to meet the energy needs of the “Torre Solar” farm, located in the rural area of the municipality of Turbaco, department of Bolívar, in response to the socioeconomic and environmental problem that the lack of electrical system coverage in these rural areas. Basically, the design of the photovoltaic generation system was made from the required energy consumption and the contribution of solar energy from the place. For this, the specialized databases in photovoltaic energy were consulted, the calculations and sizing of the PV system components were carried out, the designed system was simulated in PSGIS and the implementation costs were determined from commercial values, fundamental for decision-making by the owner.